Analysis of crisis communication by the Prime Minister of Australia during the COVID-19 pandemic. (August 2021) - Reyes Bernard, Natalie; Basit, Abdul; Sofija, Ernesta; Phung, Hai; Lee, Jessica; Rutherford, Shannon; Sebar, Bernadette; Harris, Neil; Phung, Dung; Wiseman, Nicola
Abstract: Leadership and communication capabilities of federal leaders during crises are imperative to support and guide citizens' behaviors and emotions. The following content analysis examines crisis communication delivered by the Australian Prime Minister (PM), Scott Morrison during the COVID-19 pandemic. Communication delivered over seven months starting from the first reported case of COVID-19 in Australia, was analyzed through a process of coding to identify central organizing crisis communication frames and themes and measured against eleven main themes based on principles of Crisis and Emergency Risk Communication (CERC) recommended by the WHO and US Centers for Disease Control and Prevention. Transcripts were sourced from the PM's official website and 91 communiques were analyzed. Key epidemiological indicators and public health measures were reviewed over timeframe to examine changes in communication over the pandemic. Findings indicated that PM Morrison included many features of CERC within his official messaging. Our analysis revealed that the original framework was limited in its scope to encompass certain messages and thus the allocation of new frames, 'public health and medical advice' and 'assuring and commending the public and institutions', allowed for a more thorough analysis of communication during a novel global health pandemic. The temporal analysis demonstrated that the government's policy and communication temporally followed case numbers and relative threat of the virus. This study has provided an in-depth review of CERC during the first phase of the COVID-19 pandemic. New frames and themes for the current CERC framework are suggested which can be transferable to other crises in Australia and other countries.